Conceptual Understanding and Meanings in Chemistry and Mathematics Constructed by Students with Partial and Total Visual Impairment - Menegasso, Paulo Jose; Menezes, André Luiz Santos (An Overview of Literature, Language and Education Research Vol. 7, 2024)
Inclusion involves a sense of belonging: feeling respected and valued for who you are, and receiving support and commitment from others so you can do your best work. Before inclusion in Brazilian public schools, we highlight the case of visually impaired people in the teaching and learning process, specifically how visual impairment affects the construction of concepts and meanings in Mathematics and Chemistry. The objective was to investigate a group of students with partial and total visual impairment, aiming to construct meanings in experimental classes. Modeling was used as a methodology, based on the Theory of Semantic Fields. The results show learning in chemistry and mathematics based on the theory of the study. Although more research needs to be carried out, the results are considered positive.